+0  
 
+5
566
1
avatar
I have the problem (4x-4)^2 = (2x+9)^2 + (2x)^2. I ended up with 4x^2-34-1 = 0. Is that right? and if so, how do I factor it correctly? thank you.
Guest Jan 31, 2012
 #1
avatar+93677 
0
(4x-4)^2 = (2x+9)^2 + (2x)^2
16x 2 - 32x + 16 = 4x 2 + 36x +81 +4x 2
8x 2 - 68x - 65 = 0

Then you have to use the quadratic formula to get the 2 irrational roots.
Melody  Oct 9, 2013

15 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.